Dolores Veintimilla: The Literary Construction of Gender and Nation on the Dawn of the Ecuadorian Independence (Castilla. Estudios de Literatura, 2011)
This paper analyzes, through the disciplines of Comparative Literature and Literary Theory, the works and figure of Ecuadorian romantic poet Dolores Veintimilla. Her writings –understood as female foundational texts– help us understand the construction of different imaginaries around the nation, just a few years after the formation of the Ecuadorian state. At the same time, through the concept of gender relations, this paper seeks to contrast Veintimilla with writer Juan Leon Mera in order to explore the discipline mechanisms directed to women in some literary texts in the nineteenth century. The intention of this essay is to, ultimately, show how this woman through her essays and poems portrayed transgressions to the recently formed nation-state and to the status quo existing at the time. These transgressions, though, were quite costly because expelled her from the canonic Ecuadorian literature for some decades.